Estimation of genetic parameters for in vitro oil palm characteristics (Elaeis guineensis Jacq.) and selection of genotypes for cloning capacity and oil yield - Corrêa, Thais Roseli; Motoike, Sérgio Yoshimitsu; Coser, Sara Morra; Silveira, Gustavo da; Resende, Marcos Deon Vilela de; Chia, Gilson Sanchez (Industrial Crops and Products, 2015)
Oil palm has stood out among the promising species for biofuel production and plant improvement through cloning superior individuals is the technology that contributes most to increase oil production. However, there are no studies on the genotypes behavior regarding both in vitro performance and yield potential simultaneously. By this mean, the objective of this paper was to study the genetic control of the related characteristics to the oil palm cloning process, and to identify responsive genotypes within a collection of 32 elite materials of a commercial planting in order to select the superior genotypes for the formation of a clonal garden. Callogenesis and production of embryogenic lines, which are main characteristics related to the cloning process, presented genetic control, verified through estimates of genetic parameters: heritability, coefficient of relative variation, and selective accuracy; also indicating efficiency in the selection of superior genotypes within the evaluated set. Genotypes A-13, A-14, A-18, A-20 and A-21 were selected as superior genotypes for both characteristics, such as oil yield and in vitro performance, due to formation of embryogenic lines. This has been the first study investigating the genetic control of the cloning capacity aiming to the selection of genotypes for a clonal garden formation.
Keywords: Plant breeding; Somatic embryogenesis; Genetic control; Callogenesis; Embryogenic line